Excessive folic acid intake and relation to adverse health outcome - Selhub, Jacob; Rosenberg, Irwin H. (Biochimie, 2016)
The recent increase in the intake of folic acid by the general public through fortified foods and supplements, has raised safety concern based on early reports of adverse health outcome in elderly with low B12 status who took high doses of folic acid. These safety concerns are contrary to the 2015 WHO statement that “high folic acid intake has not reliably been shown to be associated with negative healeffects”. In the folic acid post-fortification era, we have shown that in elderly participants in NHANES 1999–2002, high plasma folate level is associated with exacerbation of both clinical (anemia and cognitive impairment) and biochemical (high MMA and high Hcy plasma levels) signs of vitamin B12 deficiency. Adverse clinical outcomes in association with high folate intake were also seen among elderly with low plasma B12 levels from the Framingham Original Cohort and in a study from Australia which combined three elderly cohorts. Relation between high folate and adverse biochemical outcomes were also seen in the Sacramento Area Latino Study on Aging (High Hcy, high MMA and lower TC2) and at an outpatient clinic at Yale University where high folate is associated with higher MMA in the elderly but not in the young. Potential detrimental effects of high folic acid intake may not be limited to the elderly nor to those with B12 deficiency. A study from India linked maternal high RBC folate to increased insulin resistance in offspring. Our study suggested that excessive folic acid intake is associated with lower natural killer cells activity in elderly women. In a recent study we found that the risk for unilateral retinoblastoma in offspring is 4 fold higher in women that are homozygotes for the 19 bp deletion in the DHFR gene and took folic acid supplement during pregnancy. In the elderly this polymorphism is associated with lower memory and executive scores, both being significantly worse in those with high plasma folate. These and other data strongly imply that excessive intake of folic acid is not always safe in certain populations of different age and ethnical/genetic background. •This is a review article which was written in response to the 2015 guidelines from the World Health Organization that: “high folic acid intake has not reliably been shown to be associated with negative health effects”.•It describes peer reviewed publication showing that excessive folic acid intake is not always safe.•In particular excessive intake of folic acid could have adverse health outcome in elderly with vitamin B12 deficiency, particularly with respect to cognitive function and anemia.•Other studies show diverse adverse effects, including lower natural killer cell activity in elderly women, increase in insulin resistance in offspring of mothers from India with high folic acid intake and increase in incident of breast cancer and other cancers in women with polymorphism of the dihydrofolate gene (19 bp deletion).